2022
DOI: 10.26848/rbgf.v15.5.p2313-2326
|View full text |Cite
|
Sign up to set email alerts
|

Previsão de Focos de Calor na Região Metropolitana de Maceió Utilizando Rede Neural Artificial

Abstract: O objetivo deste estudo é o de analisar a previsão de focos de calor (FC) na Região Metropolitana de Maceió (RMM) utilizando Rede Neural Artificial (RNA). Foram usados neste estudo os dados de focos de calor no período de 1999 a 2019, disponíveis no Banco de Dados de Queimadas (BDQueimadas). A previsão foi feita com base na RNA não linear autorregressiva (NAR) com os FC sendo dados de entrada e alvo. As previsões se basearam na função de ativação Tangente Hiperbólica e Sigmoide, para averiguar qual função se a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Maceió is in ENEB between latitudes 9.40º to 9.70º S, and longitudes 35.80º to 35.60º W, with altitudes that vary between 0 and 100 m above mean sea level (NMM), located in the Atlantic Forest biome. (Santos, et al, 2022;Batista, et al, 2021), as shown in Figure 1. According to the Köppen-Geiger classification, it is categorized as tropical hot and humid 'As', with variations in temperature throughout the year.…”
Section: Study Areamentioning
confidence: 89%
See 3 more Smart Citations
“…Maceió is in ENEB between latitudes 9.40º to 9.70º S, and longitudes 35.80º to 35.60º W, with altitudes that vary between 0 and 100 m above mean sea level (NMM), located in the Atlantic Forest biome. (Santos, et al, 2022;Batista, et al, 2021), as shown in Figure 1. According to the Köppen-Geiger classification, it is categorized as tropical hot and humid 'As', with variations in temperature throughout the year.…”
Section: Study Areamentioning
confidence: 89%
“…This ANN is characterized by the variable Z, which is the time delay. The Z factor works as a memory that provides current and previous input values (Santos, et al, 2022;Santos, et al, 2020;Samet, et al, 2019).…”
Section: Prediction Via Artificial Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations